Leadership in Action: Taking Action: A Case Study in Dynamic learning - Drath, Wilfred (Center for Creative Leadership, 2006)
A method of learning dating to the 1950s is founded on the conviction that people learn best from their experience, but only if they can reflect critically on that experience. Action learning is a way to learn while doing; it balances the action of work with shared reflection among participants about what they are learning, both as individuals and as a team or group.